Making music pay [digital music distribution]. - Cherry, S.M (IEEE spectrum)
The author argues that free Napster-style music sharing is on its way out. He believes that the future of digital music distribution will be determined by consumers voting with their purses for a single, or at most two, systems, just as they did with videotape formats and PC operating systems. Napster offered immediate gratification; regaining it will cost some privacy as well as money. As companies like Microsoft come to know all about us-not just our choices in music and films, but about our finances and even personal location-we may long for a pre-digital day. Meanwhile, you may think you are buying the right to play a song at will. In truth, as digital music payment systems emerge, you will only be buying the right to play it on devices that recognize that right and have the software to play it